2014
DOI: 10.3390/ijms150611054
|View full text |Cite
|
Sign up to set email alerts
|

A Single Nucleotide Polymorphism in the Stromal Cell-Derived Factor 1 Gene Is Associated with Coronary Heart Disease in Chinese Patients

Abstract: Coronary heart disease (CHD) is highly prevalent globally and a major cause of mortality. Genetic predisposition is a non-modifiable risk factor associated with CHD. Eighty-four Chinese patients with CHD and 253 healthy Chinese controls without CHD were recruited. Major clinical data were collected, and a single nucleotide polymorphism (SNP) in the stromal cell-derived factor 1 (SDF-1) gene at position 801 (G to A, rs1801157) in the 3'-untranslated region was identified. The correlation between rs1801157 genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…After different levels of screening, 42 articles were excluded, including 22 articles that were duplicated, 3 articles that did not concern CHD, and 17 articles that did not concern rs1801157. Seven articles were found to be in accordance with the inclusion criteria and were finally included in this meta-analysis 20 21 22 26 27 28 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After different levels of screening, 42 articles were excluded, including 22 articles that were duplicated, 3 articles that did not concern CHD, and 17 articles that did not concern rs1801157. Seven articles were found to be in accordance with the inclusion criteria and were finally included in this meta-analysis 20 21 22 26 27 28 29 .…”
Section: Resultsmentioning
confidence: 99%
“…Several GWASs have confirmed that the rs501120 and rs1746048 polymorphism loci in the SDF-1 gene are associated with the susceptibility to CHD 16 17 , but rs1801157 was not reported in any of the above studies. The cause may be that GWASs cannot identify all of the SNPs involved in a single action, although they could offer a large amount of information on SNPs 20 . Furthermore, because the rs1801157 polymorphism was demonstrated to upregulate the expression of SDF-1 19 , some researchers have suggested that rs1801157 is associated with a decreased risk of CHD 20 26 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHD is a complex disease, involving interactions between environmental and genetic factors (Feng et al, 2014). Previous studies have found that single nucleotide polymorphisms (SNPs), important genomic elements, can affect an individual's genetic susceptibility to various diseases, including CHD Muiya et al, 2014;Wu et al, 2014;Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the exact mechanism of the disease is still unclear. In recent years, genetic predisposition has been thought to be closely associated with CHD and has been widely studied [5,6].…”
Section: Introductionmentioning
confidence: 99%